PROBLEMS AND SOLUTIONS AMONG THE LANGUAGE LEARNERS (Web of Teachers: Inderscience Research, 2024)
Problems associated with language learning include things like lack of vocabulary, difficulty in understanding, psychology of the learners, shyness and other types of difficulties. Various problems associated with language learning are discussed in this article along with strategies to help learners who face such circumstances.